PENDEKATAN HERMENEUTIKA FILOSOFIS UNTUK MEMAHAMI MAKNA PROFESI GURU AGAMA DALAM DINAMIKA TUNTUTAN MUTU GLOBAL - Ma’shum Thoyib; Siti Aimah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and interpret the meaning of the religious teaching profession in facing the dynamics of global quality demands through a philosophical hermeneutic approach. The study employed a qualitative approach with a case study conducted at Al-Fath Islamic Junior High School in Pare, Kediri. Data collection techniques included in-depth interviews, participant observation, documentation, and audio analysis to comprehensively capture the experiences and meaning-making processes of religious teachers. Data analysis was conducted using the Miles and Huberman interactive model, which encompasses data reduction, data presentation, and reflective conclusion drawing. Data validity was checked through triangulation of sources, methods, and observers to ensure the validity and credibility of the research findings. The results indicate that the meaning of the religious teaching profession has shifted from a doctrinal role to an interpretive and reflective role. Religious teachers are understood as facilitators of meaning who bridge religious teachings with socio-global realities, while simultaneously navigating the tension between local-religious values ​​and global quality demands. The professionalism of religious teachers is defined as a continuous process of meaning-making supported by self-reflection, pedagogical adaptation, moral role modeling, and a synthesis of spiritual and global competencies.